Association of the degree of adiposity and duration of obesity with measures of cardiac structure and function: The CARDIA study. (13th August 2014) - Reis, Jared P.; Allen, Norrina; Gibbs, Bethany B.; Gidding, Samuel S.; Lee, Joyce M.; Lewis, Cora E.; Lima, Joao; Lloyd‐Jones, Donald; Loria, Catherine M.; Powell‐Wiley, Tiffany M.; Sharma, Shishir; Wei, Gina; et al.
<x xml:space="preserve">Abstract</x> Objective Examine whether there are independent influences of a greater degree of adiposity and longer duration of obesity on cardiac structure and function. Methods Participants of CARDIA were 18‐30 years when they underwent a baseline examination in 1985‐86. Seven follow‐up examinations were conducted every 2‐5 years. Results Among 2, 547 participants who underwent an echocardiogram at the year 25 examination and were not obese at baseline, 34.4 and 35.5% were overall (BMI ≥ 30 kg m−2) and abdominally obese (waist circumference: men: >102 cm; women: >88 cm) at year 25, respectively. A greater degree of overall and abdominal adiposity at year 25 were each associated with a greater left ventricular (LV) mass (P < 0.001), LV volume (P < 0.001), LV mass‐to‐volume ratio (P < 0.001), left atrial dimension (P < 0.001), and ejection fraction (P < 0.05) after adjustment for duration of obesity and other risk factors. In contrast, a longer duration of overall obesity was associated with a greater LV mass (P = 0.003) and a trend for a lower ejection fraction (P = 0.07). Conclusions A greater degree of adiposity is strongly associated with concentric LV remodeling in midlife, while the cumulative effects of a longer duration of overall obesity during young adulthood contribute to concentric remodeling predominantly by increasing LV mass.